E-020 Safety and Efficacy of the Pipeline Embolization Device in 100 Small Intracranial Aneurysms. (26th July 2014) - Chalouhi, N; Zanaty, M; Whiting, A; Yang, S; Tjoumakaris, S; Hasan, D; Starke, R; Hann, MS; Hammer, C; Kung, D; Rosenwasser, R; Jabbour, P
Abstract : Objective: Flow diverters are increasingly used for treatment of intracranial aneurysms. In most series, the PED was used for the treatment of large, giant, complex, and fusiform aneurysms. Little is known about the use of the PED in small aneurysms. The purpose of this study was to assess the safety and efficacy of the PED in small aneurysms (≤ 7 mm). Methods: A total of 100 consecutive patients with small aneurysms (≤ 7 mm) were treated with the PED at our institution between May 2011 and September 2013. Data on procedural safety and efficacy was retrospectively collected. Results: Mean aneurysm size was 5.2 ± 1.5 mm. Seven patients had sustained a subarachnoid haemorrhage. All except 5 aneurysms (95%) arose from the anterior circulation. The number of PEDs used was 1.2 per aneurysm. Symptomatic procedure-related complications occurred in 3 (3%) patients: 1 distal parenchymal haemorrhage managed conservatively and 2 ischemic events. At the latest follow-up (mean, 6.1 months), 52 (71%) aneurysms were completely occluded (100%), 10 (14%) were near-completely occluded (≥90%), and 11 (15%) were incompletely occluded (<90%). Six aneurysms (8%) required further treatment. Increasing aneurysm size (OR= 3.9; 95% CI: 0.99–15; p = 0.05) predicted retreatment. All patients achieved a favorable outcome (mRS 0–2) at follow-up. Conclusion: In this study, treatment of small aneurysms with the PED was associated with low complication rates and high aneurysm occlusion rates. These findings suggest that the PED is a safe and effective alternative to conventional endovascular techniques for small aneurysms. Randomised trials with long-term follow up are necessary to determine the optimal treatment that leads to the highest rate of obliteration and best clinical outcomes. Disclosures: N. Chalouhi: None. M. Zanaty: None. A. Whiting: None. S. Yang: None. S. Tjoumakaris: None. D. Hasan: None. R. Starke: None. S. Hann: None. C. Hammer: None. D. Kung: None. R. Rosenwasser: None. P. Jabbour: None.